2012
DOI: 10.1037/a0028764
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling stereotype activation and stereotype application in the stereotype misperception task.

Abstract: When forming impressions about other people, stereotypes about the individual's social group often influence the resulting impression. At least 2 distinguishable processes underlie stereotypic impression formation: stereotype activation and stereotype application. Most previous research has used implicit measures to assess stereotype activation and explicit measures to assess stereotype application, which has several disadvantages. The authors propose a measure of stereotypic impression formation, the stereoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(162 citation statements)
references
References 85 publications
3
155
0
Order By: Relevance
“…Depending on the context, different stereotypes may be activated. In Study 3, we investigated if the reported effects of cardiovascular interoceptive signals can be generalized to positive racial associations portraying Black individuals as athletic3536. The sport-fruits identification task35 is a modified version of the WIT in which participants were required to discriminate between pictures of fruits and sport-objects preceded by pictures of White or Black faces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the context, different stereotypes may be activated. In Study 3, we investigated if the reported effects of cardiovascular interoceptive signals can be generalized to positive racial associations portraying Black individuals as athletic3536. The sport-fruits identification task35 is a modified version of the WIT in which participants were required to discriminate between pictures of fruits and sport-objects preceded by pictures of White or Black faces.…”
Section: Resultsmentioning
confidence: 99%
“…Here, participants had to discriminate between pictures of fruits (for example, apple, grapes, cherries) and sport-objects (for example, basketball ball, weights, skateboard)35. This task taps into the stereotype of Black individuals as athletic3536. Ten black and white pictures of each stimuli category were used.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the possibility that participants could identify targets based on repeated presentation, I rotated each image by 90 degrees to produce 4 orientations for a total set of 40 target stimuli. Finally, I implemented a third set of neutral control prime images that consisted of the outline of a face (see [52]).…”
Section: Independent Replication Of Payne (2001)mentioning
confidence: 99%
“…For example, task switching ability (e.g., Mierke & Klauer, 2003), stimulus recoding into figure-ground discriminations (e.g., Rothermund, Wentura, & De Houwer, 2005), and response criterion setting processes (e.g., Klauer, Voss, Schmitz, & Teige-Mocigemba, 2007; for a review, see Teige-Mocigemba, have all been proposed to contribute to IAT performance. Several formal models incorporate non-associative processing components to explain performance on other implicit measures, including application of Jacoby's (1991) process dissociation procedure to a variety of measures (for a review, see Payne & Bishara, 2009), the ABC model (Stahl & Degner, 2007) of performance on the EAST (De Houwer, 2003), Nadarevic and Erdfelder's (2011) Trip model of performance on the GNAT (Nosek & Banaji, 2001), Payne and colleagues' (Payne, Hall, Cameron, & Bishara, 2010) account of performance on the AMP (Payne, Cheng, Govorun, & Stewart, 2005), and Krieglmeyer and Sherman's (2012) multiprocess account of stereotype activation and application on the SMT. Each of these models provides evidence that both associations and non-associative processes contribute to responses on implicit attitude measures.…”
Section: Introductionmentioning
confidence: 99%